Standby mode minimization for efficient building management system using fuzzy logic - Waqar, Tariq (2015)
In regards of smart and efficient energy management, many think that standby mode purely the solution in reducing the electrical usage. However, the standby mode of electrical appliances is also among one of the main factors that contributes to the electrical wastage as the appliances still consumes electrical energy during the standby operation. This research mainly focuses on creating a FES with a combination of image processing that minimize the standby mode and to evaluate the performance of the created dummy load system based by real-time lecture room case studies. The problem statement on energy wastage is strongly upheld by all previous studies done on this respective issue. The outcome of this research can be used to enhance the existing Building Management System (BMS) with the addition of standby mode minimization automation system. With this research, the standby mode of the electrical appliances can be automatically and manually controlled or minimized based on the desired fuzzy rules set by the feedback system of image processing intact by the system. The role of image processing in this system is as same as of occupancy sensor, but the role of camera image processing filters makes it feedback more precise. The controlling of the electronic devices like TV, LCD, Gaming consoles or mobile and laptop chargers are totally dependent on the presence of the user in the premises or for charging and discharging phenomenon load detection circuit is used in this proposed research. Overall the proposed research can be explained as the system is comprised of fuzzy logics and rules which are monitoring and controlling the power consumption of electronic and electrical devices. Whereas controlling and monitoring is done through GUI developed in Matlab and controlling and monitoring is done with sets of fuzzy rules with the feedback of image processing with the use of filters to make the feedback more accurate and precise for this purpose GAIT reorganization system. It addresses the main point of concern that is the minimization of the standby operation of electrical appliances.